(untitled) (Informatica, 2022)
As an important supplement to my country’s financial institutions, micro-loan companies serve "agriculture, rural areas and farmers", small and micro enterprises, and individuals, to a certain extent, alleviating the financing difficulties of such groups and regulating private finance. However, micro-loan companies only lend but do not deposit. In the process of lending, due to inadequate risk management, the risk problem has become increasingly prominent. With the continuous growth of the loan amount of rural credit and the continuous increase of microfinance groups lending customers, it faces certain problems in its risk management, which increases the risks of the company in all aspects. The performance evaluation of sustainable microfinance groups lending is a classical multiple attribute decision making (MADM) issues. In this given paper, the interval-valued intuitionistic fuzzy sets (IVIFSs), Hamacher operation sum and Hamacher operation product are introduced. The induced interval-valued intuitionistic fuzzy Hamacher power OWA (I-IVIFHPOWA) operator is built. Then, the I-IVIFHPOWA information operator is employed to solve MADM under IVIFSs. Finally, an example for performance evaluation of sustainable microfinance groups lending is used to test this new defined approach.